The impact of Asian financial crisis towards Malaysian economy / Mohamad Shahdan Yusof - Yusof, Mohamad Shahdan (Faculty of Business Management, 2017)
The purpose of conducting this study is to investigate the relationship between inflation rate represented by consumer price index, exchange rate per Malaysia Ringgit against US Dollar, and Interest rate towards economic growth of Malaysia. It covers the period 1997 to 2016 quarterly which consist of 80 observations. Simply put, those determinants are considered as indicators for economic growth in Malaysia. Inflation rate represented by consumer price index, exchange rate per Malaysia Ringgit against US Dollar, and interest rate were use as independent variable. Unit root test and diagnostic test were being used to test whether it is stationary or non-stationary. The analyses are conducted using multiple linear regressions to get the results. The result shows that Inflation and interest rate has a significant and negative relationship towards economic growth. However, the result also shows that the exchange rate insignificantly affecting the economic growth. Overall, the model is significant as the p-value is less than the significant level of (0.000051) which is less than 0.1 significant levels. The null hypothesis has been rejected because F-statistic is statistically significant at 1% significant level.